Data Justice and the Right to the City - Currie, Morgan; Knox, Jeremy; McGregor, Callum (Edinburgh University Press, 2023)
Data Justice and the Right to the City engages with theories of social justice and data-driven urbanism. It explores the intersecting concerns of data justice - both the harms and civic possibilities of the datafied society - and the right to the city - a call to redress the uneven distribution of resources and rights in urban contexts. These concerns are addressed through a variety of topics: digital social services, as cities use data and algorithms to administer to citizens; education, as data-driven practices transform learning and higher education; labour, as platforms create new precarities and risks for workers; and activists who seek to make creative and political interventions into these developments. This edited collection proposes frameworks for understanding the effects of data-driven technologies at the municipal scale and offers strategies for intervention by both scholars and citizens.